2016
DOI: 10.1016/j.molcel.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Pairing beyond the Seed Supports MicroRNA Targeting Specificity

Abstract: SUMMARY To identify endogenous miRNA target sites, we isolated AGO-bound RNAs from Caenorhabditis elegans by individual-nucleotide resolution crosslinking-immunoprecipitation, which fortuitously also produced miRNA-target chimeric reads. Through the analysis of thousands of reproducible chimeras, pairing to the miRNA seed emerged as the predominant motif associated with functional interactions. Unexpectedly, we discovered that additional pairing to 3′ sequences is prevalent in the majority of target sites and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
355
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(404 citation statements)
references
References 52 publications
(112 reference statements)
23
355
2
1
Order By: Relevance
“…The performance 672 gap between miRAW and the descriptor-based approaches suggests that current 673 knowledge is still not sufficient to accurately capture all aspects of the miRNA targeting 674 process. This is consistent with recent studies, e.g., [3], [7] and [31], which 675 demonstrate that the whole miRNA can play a relevant role in many functional miRNA 676 targets. Based on these findings, we took advantage of deep learning methodology to 677 incorporate the whole miRNA sequence for target prediction.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The performance 672 gap between miRAW and the descriptor-based approaches suggests that current 673 knowledge is still not sufficient to accurately capture all aspects of the miRNA targeting 674 process. This is consistent with recent studies, e.g., [3], [7] and [31], which 675 demonstrate that the whole miRNA can play a relevant role in many functional miRNA 676 targets. Based on these findings, we took advantage of deep learning methodology to 677 incorporate the whole miRNA sequence for target prediction.…”
supporting
confidence: 89%
“…This seed-centric 15 view has been supported by structural studies [5] and a widely cited report [6] that 16 investigated the importance of other (non-canonical) regions within a miRNA and 17 concluded their contributions had relatively low relevance compared to the (canonical) 18 seed region. However, more recent studies have revealed that many relevant targets are 19 implemented via non-canonical binding and involve nucleotides outside the seed region, 20 indicating that the entire miRNA should be considered in target prediction 21 algorithms [3,7,8]. This is also supported by the performance of target prediction tools 22 which typically identify approximately 80% of known miRNA targets, indicating the 23 mechanisms associated with the remaining 20% of non-canonical targets remain poorly 24 understood.…”
mentioning
confidence: 99%
“…Thus, in this biological context, the miR-790/791 family members are not redundant. This in vivo example lends credence to recent biochemical studies that have shown specific target-binding activity by distinct miRNA family members (Moore et al 2015;Broughton et al 2016). The second implication of this study is that a single miRNA, even a poorly conserved one, can have a function essential to animal survival in the wild.…”
supporting
confidence: 73%
“…In a recent study, it was reported that the 3 0 region of miRNA contributes to the specific binding of miRNAs from the same family into target mRNAs. 25 However, this finding does not apply to our results, because the number of base-pairs between 3 0 region of miRNA and target mRNA was similar between the binding of miR-221 and miR-222 into CDKN1C (Fig. S2).…”
Section: Discussionmentioning
confidence: 57%